2019
DOI: 10.3389/fnagi.2019.00250
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on the Association Between Grip Strength and Cognitive Function Among Middle-Aged and Elderly Chinese Participants

Abstract: ObjectiveTo study the efficacy of grip strength (GS) as a predictor of cognitive function in a large, nationwide sample of Chinese participants aged 45 years and above.MethodsWe used data from three waves (W1, W2, and W3) fielded by the China Health and Retirement Longitudinal Study (CHARLS). Cognitive function was tested biennially and calculated using two categories: episodic memory and mental intactness. Demographics, health behaviors, and medical conditions were considered potential confounders. Using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…hand grip, toe grip, gait) support this argument. [37][38][39] Sociodemographic variables, such as age, education, and marital status, have been found to be significant predictors of cognitive decline in previous studies. In particular, age was a powerful predictor of cognitive impairment.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…hand grip, toe grip, gait) support this argument. [37][38][39] Sociodemographic variables, such as age, education, and marital status, have been found to be significant predictors of cognitive decline in previous studies. In particular, age was a powerful predictor of cognitive impairment.…”
Section: Introductionmentioning
confidence: 89%
“…7,35 Interestingly, some researchers have argued that hand grip strength is a preventive factor of cognitive decline. [36][37][38] The similarities in the brain areas and networks involved in cognition and muscle strength (e.g. hand grip, toe grip, gait) support this argument.…”
Section: Introductionmentioning
confidence: 93%
“…In fact, over 210 large‐scale longitudinal studies archived in the Inter‐university Consortium for Political and Social Research (ICPSR) report at least one wave of grip strength data in their samples. Although it is generally accepted as a measure of physical or motor function, there is a growing number of studies that have demonstrated its statistically significant relationship to cognition, either cross sectionally/at baseline 2–9 or longitudinally 2,3,7,10–14 in both non‐demented and demented samples. This statistical relationship has coined the phrase, ‘People who grip better, think better’, 8 and suggests that motor or physical function (i.e., neural drive to skeletal muscle) and certain cognitive functions share overlapping neurological processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, grip strength has been shown to predict decline in several cognitive abilities in non‐demented older adults 4,16 . As a result, it has been interpreted that ‘maximum grip strength testing provides a discriminating measure of neurological function’, making it a potentially valuable motor measure that may track with, 2,7 or even precede, 2,3,12,16,17 declines in cognition, perhaps as early as middle‐age 11 …”
Section: Introductionmentioning
confidence: 99%
“…It is likely a combination of the two scenarios. There is evidence that poor muscle strength (measured by handgrip) and slow gait speed are good predictors of AD development in future years [ 9 , 10 , 11 ]. This data suggests that poor indices of strength and physical function occur prior to AD diagnosis.…”
mentioning
confidence: 99%